Mediating Roles of Self-Control and Social Support in the Relationship Between Problematic Internet Use and Depression Among Korean Children and Adolescents - Lee, Cheongwoo; Park, Subin (Journal of korean Academy of Child and Adolescent Psychiatry, 2025)
This study examined whether self-control and perceived social support mediated the relationship between problematic Internet use (PIU) and depression in Korean adolescents and whether these pathways differed by PIU risk level based on the Korean version of the Young Internet Addiction Test (YIAT; cutoff=40). This study analyzed data from 2294 adolescents in a nationally representative cohort. The participants completed the YIAT, Children's Depression Inventory, Gottfredson Self-Control Scale, and Social Support Appraisal Scale. A hierarchical regression based on Baron and Kenny's mediation framework was conducted, and serial multiple mediation was tested with subgroup analyses by risk level. PIU was significantly associated with lower self-control, lower perceived social support, and higher levels of depressive symptoms. Mediation analyses in the total sample revealed that self-control and social support partially mediated the association between PIU and depressive symptoms. The strongest indirect effect was found in the serial pathway (PIU → self-control → social support → depression; effect=0.050, 95% confidence interval, CI [0.037, 0.065]). Subgroup analyses demonstrated that self-control fully mediated this relationship in the low-risk group, whereas only partial mediation was observed in the high-risk group. In the low-risk group, the self-control-only pathway (PIU → self-control → depression) was the strongest (effect=0.071, 95% CI [0.049, 0.094]), whereas in the high-risk group, the serial path had the largest effect (effect=0.040, 95% CI [0.030, 0.051]). Self-control and social support mediated the relationship between PIU and depressive symptoms, with different patterns by risk group. Therefore, targeted interventions should consider these distinct mechanisms.